RETRACTED: Principles of intermediaries’ liability in the online environment: the issue of online self-regulation - Pokrovskaya Anna; Gronic Irina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001